2022
DOI: 10.3390/nu14030491
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestation and Diagnostic Process of Celiac Disease in Poland—Comparison of Pediatric and Adult Patients in Retrospective Study

Abstract: The diagnosis of celiac disease (CD) may be delayed due to non-specific clinical symptoms. The aim of the study was to evaluate the clinical manifestation and diagnostic process of CD in Polish children and adults. Methods: The members of the Polish Coeliac Society (n = 2500) were asked to complete a questionnaire on socio-demographic factors, clinical and diagnostic aspects of CD. The analysis was based on 796 responses from patients with confirmed CD diagnosis, and included 224 (28.1%) children and 572 (71.9… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…The basic and most effective method of CD treatment is a gluten-free diet (GFD) [ 4 ]. However, it has been shown that in more than 80% of subjects, the symptoms may persist despite a restrictive GFD [ 5 ]. The studies of our team have revealed that symptoms in Polish CD patients persisted for up to 6 years after introducing a GFD [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic and most effective method of CD treatment is a gluten-free diet (GFD) [ 4 ]. However, it has been shown that in more than 80% of subjects, the symptoms may persist despite a restrictive GFD [ 5 ]. The studies of our team have revealed that symptoms in Polish CD patients persisted for up to 6 years after introducing a GFD [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that in more than 80% of subjects, the symptoms may persist despite a restrictive GFD [ 5 ]. The studies of our team have revealed that symptoms in Polish CD patients persisted for up to 6 years after introducing a GFD [ 5 , 6 ]. One of the possible causes of persisting symptoms despite the use of a GFD may be the coexistence of other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, unrecognized and untreated allergy is a major cost factor for the management of allergic diseases [ 54 , 55 , 56 ]. Early detection of the disease and the implementation of an elimination diet can not only reduce the costs of diagnostic processes and subsequent therapy but can also significantly improve the quality of life of patients, as we have demonstrated in our research on autoimmune diseases [ 57 , 58 ]. With adherence to proper treatment and the precise diagnosis and proper management of allergic diseases, it has been estimated that even high costs can be saved [ 54 , 55 , 56 ].…”
Section: Costs Of Pamd@ In Allergy Diagnosismentioning
confidence: 99%
“…The consumption of gluten by CD-prone individuals activates innate and adaptive immune responses leading to the destruction of small intestine mucosa [ 2 , 3 ]. Although symptoms of malabsorption, such as abdominal pain, diarrhea and malnutrition, are most frequently associated with CD, the clinical picture of the disease is changing [ 4 , 5 , 6 ]. Recently, our study showed that anemia and chronic fatigue were among the most common symptoms reported by Polish CD patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%